2018
DOI: 10.1007/s10637-018-0624-7
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of non-coding RNAs in the pathogenesis, diagnosis and prognosis of osteosarcoma

Abstract: Non-coding RNAs (ncRNAs) have been found to play essential roles in various physiological and pathological processes. The involvement of ncRNAs in the development of osteosarcoma (OS) has been explored in recent years. In this review, we summarize the functions and mechanisms of microRNA, lncRNA and circRNA in the initiation and progression of OS. We specifically focused on their potential application in the diagnosis, prognosis and therapy of OS. This summary of current knowledge on the involvement of ncRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 180 publications
0
47
0
Order By: Relevance
“…It is necessary to find novel diagnostic, prognostic, and therapeutic targets for better management. Accumulating studies indicate that lncRNAs are involved in the progression of carcinogenesis for various malignancies, including OS (Smolle and Pichler, 2018;Wang et al, 2018). Therefore, lncRNAs may provide valuable biomarkers for diagnosis, prognosis, and therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is necessary to find novel diagnostic, prognostic, and therapeutic targets for better management. Accumulating studies indicate that lncRNAs are involved in the progression of carcinogenesis for various malignancies, including OS (Smolle and Pichler, 2018;Wang et al, 2018). Therefore, lncRNAs may provide valuable biomarkers for diagnosis, prognosis, and therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Long noncoding RNAs (LncRNAs) are a class of nonprotein-coding transcripts (larger than 200 bases) that participate in a variety of physiological and pathological functions (Wang et al, 2018). Increasing evidence suggests that lncRNAs play a critical role in cancer cell proliferation, migration, and apoptosis, and irregular lncRNAs levels are associated with malignancy initiation and development (Sun et al, 2018;de Oliveira et al, 2019;Flippot et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, circRNAs are involved in various cancer types and exhibit multiple effects in regulating carcinogenesis and progression 5 . However, the mechanistic and functional characterization of circRNAs in osteosarcoma is largely unknown 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence have revealed that miRNAs regulate many oncogenes and tumour suppressors in cells, and lead to initiation and progression of cancer. 21 Recent years, several miRNAs have been identified as key regulators of OS progression and excellent predictors for clinical outcome of OS patients 22,23 Decreased expression of miR-876-5p has been observed in HNSCC, HCC, ESCC and lung cancer. 14,15 Moreover, miR-876-5p underexpression is associated with poor prognostic features and reduced survival of HCC patients.…”
Section: Discussionmentioning
confidence: 99%